2014
DOI: 10.1186/1752-1947-8-195
|View full text |Cite
|
Sign up to set email alerts
|

Postsurgical Pantoea calida meningitis: a case report

Abstract: IntroductionPantoea calida, a recently described environmental Enterobacteriaceae organism, has not yet been associated with human infection.Case presentationWe report a case of postoperative meningitis caused by P. calida. After pituitary adenoma resection, a 52-year-old Caucasian woman developed febrile meningitis confirmed by cerebrospinal fluid analysis. P. calida was grown in pure culture from this fluid and was firmly identified with partial rpoB gene sequencing. She was cured by a 14-day course of merop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Similarly, Wang and Fraser have isolated P. agglomerans from the brain abscess that developed after infarction and hemicraniectomy [ 5 ]. A case report of Pantoea calida causing postsurgical meningitis in a 52-year-old female has been reported by Fritz et al [ 6 ]. Our isolation of P. agglomerans from a similar case indicates that Pantoea spp.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Wang and Fraser have isolated P. agglomerans from the brain abscess that developed after infarction and hemicraniectomy [ 5 ]. A case report of Pantoea calida causing postsurgical meningitis in a 52-year-old female has been reported by Fritz et al [ 6 ]. Our isolation of P. agglomerans from a similar case indicates that Pantoea spp.…”
Section: Discussionmentioning
confidence: 99%
“…recovered in our survey rarely cause humans harm. 30,31 However, they were able to transfer cephalosporin resistance to bacteria that do infect patients. Horizontal gene transfer will happen most frequently in areas of high bacterial density.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pantoea ananatis causes maize white spot disease (Bomfeti et al , 2008) and Pantoea agglomerans causes nosocomial infections in immunocompromised patients (Cruz et al , 2007). Fritz et al (2014) recently demonstrated that some strains of Pantoea calida were the causal agent of post-surgical meningitis in humans. Pantoea species serve as plant epiphytes or endophytes; they are also used as biocontrol agents (De Maayer et al , 2012a, b; Swart, 2009).…”
mentioning
confidence: 99%